School Health - World Bank (Washington, DC, 2012)
Ensuring that children are healthy and able to learn is an essential component of an effective education system. Good health increases enrollment and reduces absenteeism, and brings more of the poorest and most disadvantaged children to school, many of whom are girls. It is these children who are often the least healthy and most malnourished, and who have the most to gain educationally from improved health. Effective school health programs that are developed as part of community partnerships provide one of the most cost-effective ways to reach school age children, adolescents, and the broader community, and are a sustainable way to promote healthy practices. The new FRESH framework (Focusing Resources on Effective School Health) is the starting point for developing an effective school health, hygiene and nutrition program in a more child friendly and health promoting school. This Note summarizes ways to improve school health and increase educational outcomes.